The Role of the COVID-19 Handling Task Force (Covid-19 Task Force) in Ngada District - Yeremias Desidarius MUDA; Hendrik TODA; Made N.D. ANDAYANA; Primus LAKE (Journal of Tourism Economics and Policy, 2023)
This study aims to identify and describe the role of the Covid-19 task force in Ngada District. This type of research is descriptive research using a qualitative approach. The informants who became the resource persons for this research were the Chairperson of the Covid-19 Task Force for Ngada Regency, the Head of the BPBD for Ngada Regency, the Head of the Ngada Regency Police, the TNI, POLRI, SATPOL PP, people who have been exposed to Covid-19 and also people who have never been exposed to Covid-19. Total informants in this study amounted to 11 people. Data collection techniques in this study are observation, interviews, and documentation. The data that has been collected is then analyzed using data analysis techniques from Yin (2008: 34) which are dominantly carried out in case study research. The results of this study indicate that the role of the Ngada Regency Covid-19 task force has been good, especially in preventing the spread of the corona virus, but the obstacle in preventing the spread of Covid-19 is the lack of public understanding, as well as local customary habits which always cause crowds so as to spread the virus. This was difficult for the Ngada Regency Covid-19 Task Force team to overcome. The Ngada Regency Task Force Team continues to carry out its role as the unit in charge of preventing the spread of the corona virus while continuing to provide outreach, supervise and resolve problems that occur in the community.